Analisis Semiotika Roland Barthes Pada Visual Video Musik “Cosmic” Oleh Red Velvet - Fazkia Putri (VisArt: Jurnal Seni Rupa dan Design, 2026)
Red Velvet's music video "Cosmic," released on June 24, 2024, features a classic European fairy tale storybook illustration style and openly acknowledges being inspired by Ari Aster's folk horror film Midsommar (2019). Behind its bright and colorful visuals, the video conceals a hidden narrative that has rarely been examined. This study aims to uncover the denotative, connotative, and mythical meanings within the music video using a descriptive qualitative approach grounded in constructivism, guided by Roland Barthes's three-stage semiotic model. Data were collected through non-participant observation and documentation of seventeen key scenes captured as screenshots, then analyzed progressively from denotation to connotation and myth. The findings reveal that the music video constructs a pagan ritual narrative, in which a female figure who falls from the sky is captured and turned into a sacrificial offering by Red Velvet and their ritual community, ultimately transforming into a worshipped sun deity. These findings demonstrate that K-pop music videos can serve as rich objects of visual study, while also showing how Western horror myths are tamed into a narrative of worship within the South Korean creative industry